A Position Of The Birth Certificate For Child Borned A Sirri Marriage - Sarah Zettira Putri; Yefrizawati, Yefrizawati; T. Keizerina Devi; Idha Aprilyana Sembiring (Jurnal Ekonomi, 2024)
A birth certificate is a right for every child. Every child has the right to receive a birth certificate, therefore even fathers and mothers who are in unregistered marriages have children's rights protected by the state. People who want to arrange a birth certificate can come directly to the Dukcapil office or arrange it online. If the parents are not legally married then the birth certificate will contain a phrase stating that the child born from the marriage has not been registered. The formulation of the problem in this thesis is what is the mechanism for registering birth certificates for children resulting from unregistered marriages after the enactment of Law Number 24 of 2013 concerning Population Administration and Minister of Home Affairs Regulation Number 109 of 2019 concerning Forms and Books used in Population Administration in North Labuhan-batu Regency , what are the rights of those born as a result of sirri marriages with the issuance of birth certificates in North Labuhan-Batu Regency, what is the role of the Population and Civil Registration Service of North Labuhan-batu Regency in registering Birth Certificates for children resulting from sirri marriages. This paper described Through the use of Statement of Absolute Responsibility Letter (SPTJM) as an alternative to a marriage certificate, this service seeks to guarantee children's civil rights, including the right to legal identity. Despite facing various challenges and dilemmas, this service continues to try to balance legal compliance and protecting children's rights, while providing services and information to the community about procedures that can be taken to legalize marital status. Thus, the Population and Civil Registration Service plays an important role in ensuring that every child, including those born from unregistered marriages, can obtain a birth certificate and the rights that accompany it, even though there is still the potential for administrative difficulties in the future due to the parents' unregistered marital status. formally.